Platypnoea–orthodeoxia syndrome: beware of investigations undertaken supine. Issue 9 (30th May 2019) - Liew, Felicity; Gargoum, Fatma; Potter, Robert; Rosen, Stuart D; Ward, Simon; Hind, Matthew; Polkey, Michael I
Abstract : Platypnoea–orthodeoxia syndrome (POS) is a rare disorder, manifesting as deoxygenation occurring when the patient is in the upright position. Four broad mechanisms for the condition have been described: intracardiac shunts, intrapulmonary shunts, hepatopulmonary syndrome and pulmonary ventilation–perfusion mismatch. Here, we present the first case of POS in a patient with a proven right to left intracardiac shunt occurring in the context of postural hypotension and normal right heart pressures. We highlight the need to carry out investigations in the upright position before discounting intracardiac shunting as a cause for the syndrome. Short-term improvement of the syndrome was obtained with medical management of the patient's orthostatic hypotension and as such suggests a conservative management strategy for similar patients, which may delay the need for invasive procedures to close the anatomical defect.